Asprosin serum levels and glucose homeostasis in children with obesity. (June 2021) - Corica, Domenico; Aversa, Tommaso; Currò, Monica; Tropeano, Angelo; Pepe, Giorgia; Alibrandi, Angela; Ientile, Riccardo; Wasniewska, Malgorzata
Highlights: Asprosin is involved in glucose homeostasis and food intake regulation. Obese children have lower asprosin serum levels than non-obese controls. Fasting asprosin decrease with increasing BMI. Insulin-resistance does not seem to affect fasting asprosin serum levels. A self-regulatory mechanism could be involved in asprosin levels decrease. Abstract: Purpose: Asprosin is a novel adipokine involved in glucose homeostasis, food intake regulation and energy homeostasis. However, the role of asprosin in glucose homeostasis regulation remains still controversial, especially in pediatrics. Aims of the study were to compare fasting serum asprosin levels between obese children and controls and to investigate the relationships of asprosin with body mass index (BMI) and biochemical markers of insulin resistance, insulin sensitivity, β-cell function and cardio-metabolic risk in obese non-diabetic children. Methods: This cross-sectional, case-controlled, study included 43 obese children and 24 lean matched controls consecutively recruited. Children underwent clinical and biochemical assessments, including oral glucose tolerance test. Fasting asprosin serum levels were measured using an enzyme-linked immunosorbent assay (ELISA). Homeostasis model assessment of insulin resistance (HOMA-IR), homeostasis model assessment of β-cell function (HOMA-B), Matsuda-index, Insulinogenic-index, Areas Under the Curves for glucose and insulin were calculated. Successively, asprosin variable was dichotomized according to mean value in order to create two ordered classes of values. Results: Fasting asprosin concentration was significantly lower in obese children compared to controls (331.9 ± 120.5 vs 358.1 ± 74.1 pg/ml; p = 0.013). Asprosin was lower in boys than in girls (313.7 ± 59.5 vs 361.1 ± 127.2 pg/ml; p = 0.044), while BMI standard deviation score (SDS) was higher in boys compared to girls (p = 0.024). Asprosin was negatively correlated with BMI (p = 0.024), BMI SDS (p = 0.044) and male sex (p = 0.043) in the entire cohort. No significant differences in asprosin levels were demonstrated between insulin resistant and non-insulin resistant obese children. Logistic regression models documented a significant negative association between BMI SDS and dichotomized asprosin. In particular, higher BMI SDS values were associated to lower asprosin serum levels class. A receiver operating characteristic (ROC) analysis showed existence of the best cut-off for BMI SDS (+2.7 SDS) variable into discriminating patients belonging to two asprosin classes in our cohort. Conclusions: In conclusion, asprosin serum levels were significantly lower in obese children compared to control. Fasting asprosin decreased with increasing BMI, but it was not significantly affected by IR.